EKSISTENSI NYANYIAN PANJANG PADA MASYARAKAT PETALANGAN KABUPATEN PELALAWAN - ', Ardila; ', Isjoni; ', Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Regional culture is part of the national culture, and is a distinctivecharacteristic to the region to support the national culture. Therefore, it becomes ourresponsibility to nurture and develop it in order to enrich the Indonesian nation. In thecreative life of the community always produce cultural products, in Indonesia known asthe diversity of race, ethnicity, language makes Indonesia as a country rich in culturalproducts. Of the many provinces in Indonesia, the Riau province that is based on theMalay culture, the products are very well known by the people of Indonesia, regionaland even international. Among these cultures known for performing arts oral literatureSinging Long vibrant and growing area Pelalawan From past to present oral traditionsused by society Petalangan as entertainment in a variety of cultural events, such as inthe event of event marriages, circumcisions and other celebration events. The purposeof this study was to determine the Song of Long communities Petalangan Pelalawan, toknow the message of the song of Long communities Petalangan Pelalawan, to know theexistence of Songs of Long communities Petalangan Pelalawan, To determine the roleof government in the preservation Songs of Long communities Petalangan Pelalawan,and for know the perception of the younger generation of the Song of length and howinheritance. The method used in this research is the historical method and qualitativemethods. Data were obtained from interviews and analyzed in its own language. Theresearch location is in Pelalawan. When the study started from the seminar proposal tothe Final exam. Data collection techniques used were observation, interviewtechniques, technical documentation and technical literature. Results from this researchthat the message contained in stories such as The Song Long live the attitude ofdeliberation, moral and educational role in the life sciences. Long chant too much toexplain about the legal awareness of forest land regulations, persukuan and cultivationof criminal acts and deontology. If specifically they are very hard to bersilaturrahmii,but he listened to their stories can chat and tell you about their daily lives.Keywords: Existence, Song Of Long,Petalangan